Karakteristik Pemikiran Ibn Khaldun Tentang Reward Dan Punishment Dalam Pendidikan - Miftahuddin (Rayah Al-Islam, 2020)
This article was written to describe and uncover Ibn Khaldun's concept of reward and punishment methods in education. This description of thought is focused on the patterns and characteristics of concepts that include foundation, principle and implementation. The target of writing this article is finding a safer and more effective model of reward and punishment implementation in education. This article was written in qualitative descriptive methods and with the content analysis approach. The main reference in this article is al-Muqaddimah written by Ibn Khaldun. The some points can be confirmed through the author‘s analysis, among them the clarity of the foundation and principles of Ibn Khaldun in his concept of reward and punishment methods in education, both philosophical, sharia and sociological. Based on basic, sharia and realistic concepts it is possible to design a safer and more effective model of implementing reward and punishment methods.